2020
DOI: 10.3390/nano10050987
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Photocatalytic Properties of PET Filaments Coated with Ag-N Co-Doped TiO2 Nanoparticles Sensitized with Disperse Blue Dyes

Abstract: In this study, the effects of disperse blue dye-sensitization on the photocatalytic properties of the Ag-N co-doped TiO2 nanoparticles loaded on polyethylene terephthalate (PET) filaments are investigated under visible light irradiation. The microstructure and photocatalytic properties of the as-synthesized TiO2 nanocomposites, as well as the as-prepared PET filaments, are systematically characterized. The photocatalytic performance of the PET filaments coated with the Ag-N co-doped TiO2 nanoparticles sensitiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 84 publications
0
14
0
Order By: Relevance
“…The interaction of organic molecules with metal nanoparticles (NPs) is of central importance for a large number of applications in several fields, such as chemical and biological sensing [1][2][3][4], optics [5][6][7], energy [8][9][10][11], catalysis [12][13][14][15], and nanomedicine [16][17][18][19]. Many of these applications are based on the effect of the localized surface plasmon resonance (LSPR) on the absorption, emission, and scattering of molecules attached to or in close vicinity to the NP surface [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…The interaction of organic molecules with metal nanoparticles (NPs) is of central importance for a large number of applications in several fields, such as chemical and biological sensing [1][2][3][4], optics [5][6][7], energy [8][9][10][11], catalysis [12][13][14][15], and nanomedicine [16][17][18][19]. Many of these applications are based on the effect of the localized surface plasmon resonance (LSPR) on the absorption, emission, and scattering of molecules attached to or in close vicinity to the NP surface [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…3 and Figure S3) also showed cutting wavelengths for samples TiO 2 -S1, TiO 2 -S2, TiO 2 -S1-cotton, TiO 2 -S2-cotton, TiO 2 -S1-NWF and TiO 2 -S2- NWF equal to 380, 377, 368, 357, 401 and 402 nm, respectively. This different values indicated that the absorption of TiO 2 varied when this was impregnated in the fabrics due to the interaction between the particles and the substrate ( Kisch & Weiß, 2002 ; Tan et al., 2013 ; Zhang et al., 2020 ). Moreover, all DRS curves of the impregnated fabrics showed a slight tail wavelength larger than 400 nm, which was attributed to the presence of defects or surface impurities over the less crystallized TiO 2 nanoparticles ( Jiang, Long, Wu & Cai, 2011 ).…”
Section: Resultsmentioning
confidence: 99%
“…According to lattice fringe images, these periodic arrangements match with lattice spacing of (101) plane of anatase (TiO 2 ) phase and are consistent with XRD analysis. 50,51 UV-vis spectroscopy was employed to analyze interactions of nanoparticles with photon energies. Absorbance spectra of pure titania and ZA (2, 4, 6 and 8 wt%) doped TiO 2 nanomaterials are illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[11][12][13][14] Currently, some researchers undertook co-doping of titania to enhance photoactivity behavior. 15,16 These studies suggested that improved photoactivity of observed products could be due to a synergetic effect between incorporated metal ions. These research reports revealed that TiO 2 modication via co-doping may prove to be an effective technique to enhance photocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%